Cortical mapping of the optically evoked responses in channelrhodopsin-2 mouse model. - Kim, Guk Bae; Jounhong Ryan Cho; Shin, Hee Sup; Choi, Ji Hyun (Conference proceedings : ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Conference, 2011)
Little is known about the information transfer properties of large-scale neural circuit in brain system. We applied optical deep brain stimulation to define the properties of information flow within a living brain assisted by channel rhodopsin-2 (ChR2) transgenic mice, of which neurons express the light-activated ion channel. We first characterized the responses of neuronal ensemble to the impinged light with respect to stimulation parameters by co-registering local field potentials with optical stimulation. Secondly, we applied recently developed polyimide based microarray for mouse electroencephalogram (EEG) to obtain the cortical responses with respect to deep brain stimulation. Particularly, the spatiotemporal cortical mapping with respect to deep brain stimulation of primary somatosensory cortex and hippocampus CA1 were presented in this article.